Sandwiched Strut Allografts with Stem Retention to Treat Fragile Periprosthetic Femoral Fractures: A Case Report - Hyoung Tae Kim; Hyun Jun Lee; Suenghwan Jo (Medicina)
Managing periprosthetic femoral fractures is challenging, particularly in osteoporotic patients with fragile bones. Revision with a long stem is commonly considered but may fail to provide adequate fixation and stability in fragile bones. A novel approach using sandwiched strut allografts and controlled bone crushing with robust cable fixation can offer mechanical support and provide secondary stability to the loosened femoral stem and can be considered a treatment option for low-demand patients. A 73-year-old female with 23 years of hemodialysis experienced pain and instability in her right thigh following a slip. She had extremely low bone mineral density, and radiographs revealed a periprosthetic femoral fracture with a loosened femoral prosthesis, classified as Vancouver type B3. The patient underwent surgical fixation using a long anatomical plate augmented with dual strut allografts sandwiched anterior and posterior femur. Robust cable fixation was performed to partially crush the native cortical bone against the stem to enhance stability. Postoperative imaging at 18 months confirmed successful bone union and implant stability, and the patient regained preoperative functional capacity without pain. This case demonstrates that partially crushing native bone with dual strut allografts may provide stability to the loosened femoral stem and can be an effective alternative to long-stem revision surgery for patients with highly fragile bones. This approach may provide immediate mechanical stability and can be a potential treatment option for managing fragile periprosthetic femoral fractures.